Distribution of diversity of fishes in an Andean fluvial network - Daniel Valencia-Rodríguez (Revista de Biología Tropical, 2023)
Introduction: The distribution of freshwater fishes in the Colombian Andes results from the interaction between historical and recent factors. Currently, the Andean landscape is facing rapid transformation processes. However, the knowledge regarding species distribution and environmental requirements is advancing slower than the transformations underway in the fluvial networks. Objective: To understand the conformation of the fish assemblage in the middle and lower Cauca River basin, considering the local environmental context before the construction of the Ituango Dam, and quantifying β diversity and its two components (turnover and nestedness) amongst local fish communities. Methods: 58 localities were monitored during nine years (between February 2010 and November 2018), the period before the dam's operation. The species richness (α-diversity), species turnover (β-diversity), and assemblage composition were estimated for the given localities. Results: 114 species were recorded, representing ~ 49 % of the total richness of known species for the Magdalena basin. The richness distribution showed that the number of species varies among the aquatic environments. Swamps presented the most significant number of species, followed by the Cauca River, while streams had the lowest values of richness. The spatial analyses of β-diversity revealed a high variation component in the study area due to species replacement between the aquatic environments.Conclusions: The implementation of long-term monitoring allowed us to recognize that the Cauca River basin conserves a great variety of species-rich environments. The species turnover indicates a high proportion of endemism or multiple sites with unique species. Finally, our study will serve as a baseline to verify, over time, whether the dam's construction is associated with essential changes in the structure of fish communities.